KONSTRUKSI PEMBERITAAN PPKM JAWA BALI PADAMEDCOM.ID DAN CNN INDONESIA PERIODE 11 SAMPAI 25JANUARI 2021 (Analisis Framing Robert N Entman) - Alfi Syahrinur (2022)
This study aims to see how the news framework for the Java-Bali Community Activity Restriction (PPKM) policy made by Medcom.id and CNN Indonesia for the period 11 January to 25 January 2021 based on Health, Economic, and Social aspects. Using Robert N. Entman's framing model and using the theory of social reality construction. The method used is a qualitative construction using data sources in the form of 36 news documents, 20 reports on Medcom.id and 16 reports on CNN Indonesia. The sampling technique was carried out by purposive sampling. Researchers took news from the period 11 to 25 January 2021 with a predetermined unit of analysis and data collection techniques. The results of this study found that both Medcom.id and CNN Indonesia both construct PPKM issues that have an impact on the economy and assess the existing regulations in PPKM such as restaurant consumers eating or drinking on the spot is twenty five percent and spending restrictions. Central operating hours such as malls, which must close at 19.00 WIB are considered by Medcom.id and CNN Indonesia to be burdensome for business actors. It's just that the author sees different constructions with a focus on PPKM reporting that leads to the economic aspect, Medcom.id for example, construction that is made more towards PPKM which has an impact on business actors, especially mall entrepreneurs, and CNN Indonesia which focuses on PPKM rules that have an impact on business actors. . such as hotel and restaurant entrepreneurs. The results of this study also look at CNN Indonesia which focuses its attention on the health aspect by framing the news that the PPKM carried out by the government is not yet fully optimal, there are still many cases of the Covid-19 spike so that many cases of Covid-19 red zones were found in its implementation, for that CNN Indonesia in many reports also recommend tightening health protocols and ask the government to increase early examinations for testing, tracing, and treatment, 3T.